Adolescent but Not Parent Report of Irritability Is Related to Suicidal Ideation in Psychiatrically Hospitalized Adolescents. Issue 2 (2nd April 2016) - Frazier, Elisabeth A.; Liu, Richard T.; Massing-Schaffer, Maya; Hunt, Jeffrey; Wolff, Jennifer; Spirito, Anthony
Abstract : Objective: Identifying trans-diagnostic risk factors for suicidality may improve assessment and treatment. This study examined the degree to which clinician ratings of adolescent irritability, based on adolescent versus parent report, were associated with adolescent suicidal ideation beyond established risk factors (i.e., female gender, depressive, substance use, oppositional defiant, conduct, and post-traumatic stress disorders). Methods: Hierarchical linear regression was used to analyze 322 adolescent inpatients (40.4% male) and 197 parents. Results: Adolescent-rated irritability (p<0.001) and depression (p<0.001) were positively associated with adolescent suicidal ideation beyond all other factors. Parent-rated adolescent irritability was unrelated to adolescent suicidal ideation. Conclusion: Results suggest irritability is an important factor in determining suicide risk, and adolescent report of irritability may be more important in gaging suicide risk than parent report.